A systematic review and meta‐analysis of progestogen use for maintenance tocolysis after preterm labor in women with intact membranes. Issue 1 (18th October 2015) - Eke, Ahizechukwu C.; Chalaan, Tina; Shukr, Ghadear; Eleje, George U.; Okafor, Charles I.
Abstract: Background: The use of progestogens for maintenance tocolysis remains controversial, with randomized controlled trials having conflicting results on their efficacy. Objectives: To evaluate the use of progestational agents for maintenance tocolysis after preterm labor in a systematic review of randomized controlled trials. Search strategy: Electronic databases were searched for reports published before December 2014. Keywords included "tocolysis, " "progesterone, " "preterm labor, " "17‐alpha‐hydroxyprogesterone, " and "vaginal progesterone." Selection criteria: Only randomized controlled trials involving progestational agents for maintenance tocolysis were included. Data collection and analysis: Outcomes were analyzed on an intent‐to‐treat basis and meta‐analysis was performed where appropriate. Relative risks and mean differences with 95% confidence intervals were calculated. Main results: Four studies (362 women) were included. There were no significant differences between progestational agents and placebo/no treatment in terms of delivery before 34 weeks or before 37 weeks of pregnancy, time from randomization to delivery, and respiratory distress syndrome. Progestogens were associated with an increase in the neonatal birth weight (mean difference 203.32 g, 95% confidence interval 110.85–295.80; P = 0.032). Conclusions: The current evidence does not support the routine use of progestational agents for maintenance tocolysis after an episode of preterm labor.